Exam Anxiety and Its Associated Risk Factors Among Indian Medical Undergraduates - Anubhuti Sharma; Satya Prakash Singh; Saket Shekhar; Poonam Kushwaha; Anju Gahlot (Medsci Publications, 2023)
Background: Exam anxiety is a global troublesome psychological problem, impairing the academic performance of medical students. This study was planned to estimate the prevalence and associated risk factors of Exam anxiety among Indian medical students Methodology: A cross-sectional analytical study was conducted among 230 Indian medical undergraduate students. Westside Test Anxiety Inventory (WTAI) was used to estimate the level of Exam anxiety among medical students. We utilized multivariable logistic regression to identify independent risk factors among medical students. Results: The prevalence of high Exam Anxiety among medical students was 49.6 % (95% CI 43.9-57.0). The mean age of the students was 21.3 years. Multivariable logistic regression revealed the presence of excessive course load [AOR=2.22,95% CI:(1.03,4.78)], the presence of psychological stress [AOR=2.89,95% CI:(1.51,5.48)] and low self-esteem [AOR=8.15,95% CI:(1.51,43.96)] to be independent risk factors for exam anxiety. Conclusions: Our study findings suggest that the prevalence of Exam anxiety is very high among Indian undergraduate medical students. Our study also showed that the perception of excessive course load, psychological stress and low self-esteem were the independent risk factors in medical students.